ANALYSIS OF HEAVY EQUIPMENT PERFORMANCE ON THE PROBOLINGGO-BANYUWANGI TOLL ROAD PROJECT KM SECTION KM 09 + 125 TO KM 09 + 725 - BILHAN GAMALIEL HARTANTO; YONAS PRIMA ARGA RUMBYARSO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Infrastructure projects, especially in flexible pavement works, are highly dependent on the utilization of heavy equipment. The use of such heavy equipment is an important element that determines the success of asphalt road construction, with the production capacity of heavy equipment being a major factor in the progress of project implementation. Therefore, the analysis of production volume capacity is very important. This study aims to determine the production volume capacity of construction works on the Probolinggo - Banyuwangi Toll Road KM 09+125 to KM 09+725, including an analysis of the capacity of asphalt finisher, dump truck, pneumatic tire roller, and tandem roller. The volumetric method was applied in this study to calculate the volume capacity and productivity of heavy vehicles. The results of the analysis showed that the calculated volume and productivity of the heavy equipment had met the target according to the planned schedule.